Hepatitis A virus cDNA and its RNA transcripts are infectious in cell culture. - Cohen, J I (1987)
A full-length cDNA copy of an attenuated, cell culture-adapted hepatitis A virus (HAV HM-175/7 MK-5) genome was constructed in the PstI site of plasmid vector pBR322. Transfection of monkey kidney cells with this plasmid failed to induce the production of hepatitis A virus (HAV). The HAV cDNA was excised from pBR322 and inserted, without the oligo(dG) X oligo(dC) tails, into an RNA transcription vector to yield plasmid pHAV/7. Transfection of monkey kidney cells with pHAV/7 DNA induced HAV infection. Transfection with RNA transcripts produced in vitro from pHAV/7 yielded about 10-fold more HAV than did transfection with pHAV/7 DNA. Marmosets inoculated with transfection-derived virus developed anti-HAV antibodies and had liver enzyme patterns that closely resembled the liver enzyme patterns seen in animals inoculated with virus from a comparable level of cell culture passage. Infectious RNA transcripts from HAV cDNA should be useful for studying the molecular basis of cell culture adaptation and attenuation as well as for studying specific viral functions.